Keterlibatan Produk dan Keterlibatan Situasional dalam Mmemoderasi Pengaruh Kepuasan Konsumen Terhadap WOM - Saraswatiwulandari, Kt Irma; Santika, I Wayan (E-Jurnal Manajemen, 2014)
14.00 This study aims to determine the effect of customer satisfaction on Word of Mouth (WOM); moderating role of product involvement on consumer satisfaction on WOM influence; and the role of moderating effect of situational involvement on consumer satisfaction on WOM provider TELKOMFlexi customers in Denpasar. Sampling was conducted using a two-stage judgment sampling the number of respondents is 40 people. Research data collection was conducted through questionnaire method with moderate regression analysis as data analysis techniques . These results indicate that customer satisfaction and a significant positive effect on WOM. In addition it is also proved that the product involvement significantly positively strengthen the influence of customer satisfaction with WOM. Situational involvement significantly positively strengthen the influence of customer satisfaction on WOM. Keywords : customer satisfaction , product involvement , situational involvement , word of mouth Normal 0 false false false EN-AU X-NONE X-NONE
Keywords: customer satisfaction , product involvement , situational involvement , word of mouth